Pengaruh Idealisme, Relativisme, dan Etika pada Persepsi Mahasiswa Akuntansi atas Perilaku Etis Akuntan - Ariyanti, Ni Made Hanny; Widanaputra, A.A.G.P (E-Jurnal Akuntansi; Vol 24 No 3 (2018), 2018)
This reseacrh about ethical behavior of accountants is influenced by idealism, relativism, and ethics. Ethical behavior is the behavior of a person acting in accordance by laws, regulations, and morals. This reseacrh examine influence of ethics to perception of nonregular students majoring in accounting Faculty of Economics and Business Udayana University by ethical behavior of accountants. This research used primary data collected by using questionnaires as instrument of data collection distributed to respondents. Respondents of this research are 127 student as sampel by non-probality sampling method of non-regular students majoring in accounting class of 2014 Faculty of Economics and Business Udayana University. The results by using multiple linier regression is idealism positively affect the perception of accounting students, relativism negatively affect the perception of accounting students for ethical behavior of accountants and ethics have a positive effect on the perception of accounting students for ethical behavior of accountants. Keywords: idealism, relativism, ethics and ethical conduct of accountants